Home-Based HIIT and Traditional MICT Prescriptions Improve Cardiorespiratory Fitness to a Similar Extent Within an Exercise Referral Scheme for At-Risk Individuals - Hesketh, Katie; Jones, Helen; Kinnafick, Florence; Shepherd, Sam O.; Wagenmakers, Anton J. M.; Strauss, Juliette A.; Cocks, Matthew (Frontiers in Physiology, 2021)
Exercise referral schemes (ERS) are used to promote physical activity within primary care. Traditionally, ERS are conducted in a gym or leisure-centre setting, with exercise prescriptions based on moderate-intensity continuous training (MICT). Home-based high-intensity interval training (Home-HIIT) has the potential to reduce perceived barriers to exercise compared to traditional MICT prescription used with ERS and improve health related outcomes. We hypothesized that Home-HIIT would mediate greater improvement in cardiorespiratory fitness (CRF) by virtue of greater adherence and compliance to the exercise prescription, compared to MICT. Methods: Patients enrolled on an ERS (Liverpool, UK) were recruited for a pragmatic trial. Participants self-selected either 12wks of MICT (45-135min/wk at 50-70% HRmax) or Home-HIIT (4-9x1min intervals at ≥80% of HRmax, interspersed with 1min rest). The primary outcome was the change in CRF (VO2peak) at post-intervention (12wks) and follow-up (3-month post intervention), using intention-to-treat analysis. Results: 154 participants (age 48±10y; BMI 30.5±6.1kg/m2) were recruited between October 2017 and March 2019, 87 (56%) participants chose Home-HIIT and 67 (44%) MICT. VO2peak increased post-intervention in both groups (MICT 3.9±6.0ml.kg-1.min-1, Home-HIIT 2.8±4.5ml.kg-1.min-1, P<0.001), and was maintained at follow-up (P<0.001). Fat mass was only reduced post MICT (MICT -1.5±6.3kg, P<0.05, Home-HIIT -0.2±2.0kg, P=1.00), but the reduction was not maintained at follow-up (MICT -0.6±5.1kg, Home-HIIT 0.0±2.2kg, P>0.05). Adherence to the prescribed programmes was similar (MICT 48±35%, Home-HIIT 39±36%, P=0.77). Conclusion: This is the first study to evaluate the use of Home-HIIT for individuals in a primary care setting. Contrary to our hypothesis adherence to both exercise prescriptions was poor, and CRF improved to a similar extent in both groups with improvements maintained at 3-month follow-up. We provide evidence that, although not superior, Home-HIIT could be an effective and popular additional exercise choice for patients within primary care based ERS.